Intra and Extracellular Journey of the Phytohormone Salicylic Acid - Maruri-López, Israel (Front Plant Sci, 2019)
Salicylic acid (SA) is a plant hormone that has been described to play an essential role in the activation and regulation of multiple responses to biotic and to abiotic stresses. In particular, during plant-microbe interactions, as part of the defense mechanisms, SA is initially accumulated at the local infected tissue and then spread all over the plant to induce systemic acquired resistance at non-infected distal parts of the plant. SA can be produced by either the phenylalanine or isochorismate biosynthetic pathways. The first, takes place in the cytosol, while the second occurs in the chloroplasts. Once synthesized, free SA levels are regulated by a number of chemical modifications that produce inactive forms, including glycosylation, methylation and hydroxylation to dihydroxybenzoic acids. Glycosylated SA is stored in the vacuole, until required to activate SA-triggered responses. All this information suggests that SA levels are under a strict control, including its intra and extracellular movement that should be coordinated by the action of transporters. However, our knowledge on this matter is still very limited. In this review, we describe the most significant efforts made to date to identify the molecular mechanisms involved in SA transport throughout the plant. Additionally, we propose new alternatives that might help to understand the journey of this important phytohormone in the future.